Heartbeat of the people : music and dance of the northern pow-wow - Browner, Tara, 1960- (Music in American life., 2002)
The intertribal pow-wow is the most widespread venue for traditional Indian music and dance in North America. Heartbeat of the people is an insider's journey through the dances and music, the traditions and regalia, and into the functions and significance of these vital cultural events. Tara Browner comes to the pow-wow as a participant--she is a dancer of Oklahoma Choctaw heritage--as well as a scholar. Focusing on the Northern pow-wow, which derives from the northern Great Plains and Great Lakes region, Browner presents an in-depth discussion of the pow-wow's roots and traditions, protocols, and order of events. She also describes footwork, styles of singing, and the diversity of participants' regalia. Browner centers her discussion of the Northern-style pow-wow around the Lakota Sacred Hoop and the Anishnaabeg Sacred Fire. Browner traces the history of specific events such as the Grass and Jingle Dress dances and distinguishes among various dance types, including Traditional, Fancy, and "special" exhibition dances as well as ceremonial honor dances, giveaways, and memorials. She also discusses women's changing roles within pow-wow performance and thoughtfully examines how continually changing musical repertories, dance styles and regalia, and customs foster a vibrant state of transformation that coexists, often uneasily, with more traditional Native mores. She closes her study with a series of interviews with members of two families of pow-wow dancers, one Lakota and one Anishnaabeg